IMPLEMENTASI KEBIJAKAN KURIKULUM BERBASIS LINGKUNGAN HIDUP DI SMK NEGERI PERTANIAN TERPADU PROVINSI RIAU - M. Dede Rosza Eriawan; Azhar Azhar; Rr. Sri Kartikowati (Jurnal Manajemen Pendidikan Penelitian Kualitatif, 2020)
This research aimed to gain an understanding the process implementation of curriculum based environment policy in SMK Negeri Pertanian Terpadu Provinsi Riau. The sub focus research consist of 1).  The programs of excellent in the implementation of curriculum based environment policy, 2). The contribution of school citizens in the implementation of curriculum based environment policy, and 3). The achievement of implementation curriculum based environment. Data was collected by interview, observation, and documentation. The results found that implementation of the curriculum based environment policy in SMK Negeri Pertanian Terpadu Provinsi Riau was implemented through flagship programmes in the form of lessons subjects, extracurricular, conditioning of infrastructure and the routine activities of the school. Citizen of school contribute to succeed the implementation of the programmes by means of school creation and inovation, utilizing partner school as tutor, and build partnership for environmental learning. The school’s achievements in implementing curriculum based environment can be seen from the school’s achievements, relationships with partner schools, and achievement of the school vision.